A systematic review of the effectiveness of epilepsy education programs on knowledge, attitudes, and skills among primary school learners - Makhado, Thendo Gertie; Sepeng, Nombulelo Veronica; Makhado, Lufuno (Frontiers in Neurology, 2024)
Epilepsy is a common neurological condition affecting primary school learners, often leading to misconceptions, stigma, and limited social inclusion. These misconceptions transpire because of a lack of knowledge regarding the condition and may lead to high school dropouts. This systematic review aimed to evaluate the effectiveness of epilepsy education programs on epilepsy-related knowledge and understanding, values and attitudes, and skills among primary school learners. A thorough search of electronic databases was conducted to identify relevant studies published between January 2000 and September 2023. Studies that satisfied the eligibility criteria were chosen, and two reviewers conducted data extraction independently. A narrative synthesis approach was utilised to analyse the findings. The review included 10 studies that satisfied the inclusion requirements. The epilepsy education interventions varied in content, duration, and delivery method. Findings indicated that diverse delivery methods, such as classroom-based programs, hospital-based programs, and community-centred interventions, effectively enhanced epilepsy-related knowledge and understanding, values and attitudes, and skills among primary school learners. This systematic review provides evidence that epilepsy education programs can effectively enhance epilepsy-related knowledge, understanding, values, attitudes, and skills among primary school learners. These findings support developing and implementing comprehensive guidelines for teaching epilepsy in primary schools, suggesting various delivery methods and integrating cultural values to promote optimal learning outcomes and social inclusion for learners with epilepsy.